E-MARKETING PADA DEALER MOTOR TVS CABANG UNIT 2 BERBASIS WEB - Aulia Mustika Sari; Dedi Darwis; Dartono Dartnono (Jurnal Ilmiah Infrastruktur Teknologi Informasi, 2021)
TVS motor is one of private company that move in manufacturing two-wheeled who was in unit 2. TVS have started to invest in indonesia since 2006. Meanwhile in lampung own TVS official open in 2009. In the marketing process, they are several problems were found on motorcycle marketing. In doing the promotion, the company was struggling to give more clear information about that product on sale. Because the marketing only done by spreading brochures. To help the motorcycle marketing system on a TVS dealer the branch of unit 2, so that lead e-marketing system based on web. This designing system uses PHP programming system and MySQL database. To marketing strategy uses SOSTAC method and to development Uses Linear Sequential Model.  By the construction of this system so that is expected to help the marketing process easier in TVS dealer the branch of unit 2.